Clinical and molecular analyses of Beckwith–Wiedemann syndrome: Comparison between spontaneous conception and assisted reproduction techniques. Issue 10 (2nd August 2016) - Tenorio, Jair; Romanelli, Valeria; Martin‐Trujillo, Alex; Fernández, García‐Moya; Segovia, Mabel; Perandones, Claudia; Pérez Jurado, Luis A.; Esteller, Manel; Fraga, Mario; Arias, Pedro; Gordo, Gema; Dapía, Irene; et al.
Abstract : Beckwith–Wiedemann syndrome (BWS) is an overgrowth syndrome characterized by an excessive prenatal and postnatal growth, macrosomia, macroglossia, and hemihyperplasia. The molecular basis of this syndrome is complex and heterogeneous, involving genes located at 11p15.5. BWS is correlated with assisted reproductive techniques. BWS in individuals born following assisted reproductive techniques has been found to occur four to nine times higher compared to children with to BWS born after spontaneous conception. Here, we report a series of 187 patients with to BWS born either after assisted reproductive techniques or conceived naturally. Eighty‐eight percent of BWS patients born via assisted reproductive techniques had hypomethylation of KCNQ1OT1 :TSS‐DMR in comparison with 49% for patients with BWS conceived naturally. None of the patients with BWS born via assisted reproductive techniques had hypermethylation of H19/IGF2 :IG‐DMR, neither CDKN1 C mutations nor patUPD11. We did not find differences in the frequency of multi‐locus imprinting disturbances between groups. Patients with BWS born via assisted reproductive techniques had an increased frequency of advanced bone age, congenital heart disease, and decreased frequency of earlobe anomalies but these differences may be explained by the different molecular background compared to those with BWS and spontaneous fertilization. We conclude there is a correlation of the molecular etiology of BWS with the type of conception. © 2016 Wiley Periodicals, Inc.